2018
DOI: 10.1155/2018/8312857
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Direct and Indirect Selection and Indices in Bread Wheat (Triticum aestivumL.) Segregating Progeny

Abstract: Three selection methods including direct and indirect selection along with selection index based on the phenotypic values of eleven traits of agronomic interest were assessed for their application in F4 bread wheat progenies. Significant genetic variation existed among parents and crosses for the traits measured. The following were the most efficient indices for simultaneous selection of superior lines for yield and its components: base index of Williams, followed by the sum of ranks index of Smith and Hazel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 38 publications
4
48
0
2
Order By: Relevance
“…Mahdy et al (2012) after three cycles of direct selection for grain yield noted realized heritability of 78.46% under normal irrigation and 37.88% under drought stress. Fellahi et al (2018) noted narrow sense heritability of 10.13% for grain yield after index selection (desired grain index).…”
Section: Narrow Sense Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mahdy et al (2012) after three cycles of direct selection for grain yield noted realized heritability of 78.46% under normal irrigation and 37.88% under drought stress. Fellahi et al (2018) noted narrow sense heritability of 10.13% for grain yield after index selection (desired grain index).…”
Section: Narrow Sense Heritabilitymentioning
confidence: 99%
“…It was 19.95 and 16.5 in the first and 11.15 and 11.06 in the second year for desired gain index and was more efficient than Smith-Hazel index (ΔH = 9.58 and 8.97 in the first and 9.74 and 8.59 in the second year) under drought stress at heading and well-irrigated conditions, respectively. Fellahi et al (2018) found that the base index of Williams ranked the first followed by the Smith Hazel index for simultaneous selection of superior lines for yield and its components. Jinks andConnolly (1973 and1975) studied the relationship between selection environment and environmental sensitivity (stability) in Schizophyllum commune.…”
Section: Introductionmentioning
confidence: 99%
“…The selection criteria also determine the effectiveness of the selection method on adaptive maize screening under drought stress. In general, the line selection can be done with two approaches: direct selection and indirect selection (Costa et al 2008;Fellahi et al 2018). Direct selection is the most common selection focused on the relative decrease of yield between normal and drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this selection method is considered ineffective because productivity has low heritability under stress condition (Fritsche-Neto and DoVale 2012; Kassahun et al 2013). Therefore, the direct method approach needs to be integrated with the determination of secondary characters in supporting the yield stability of plants grown in a varied environment (Fellahi et al 2018;Anshori et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Mulamba & Mock sum of ranks index presented higher gains when compared to the Smith and Hazel index. The efficiency of using selection indexes has also been observed in silage maize (Crevelari et al, 2019), soybean (Teixeira et al, 2017), and wheat (Fellahi et al, 2018). Almeida et al (2019) showed concordance between indexes with regards to the ranking of the best genotypes; the magnitude of the expected gain must be considered.…”
Section: Discussionmentioning
confidence: 87%